A Four-Year Survey of Hemoparasites from Nocturnal Raptors (Strigiformes) Confirms a Relation between Leucocytozoon and Low Hematocrit and Body Condition Scores of Parasitized Birds - Martín-Maldonado, Bárbara; Mencía-Gutiérrez, Aida; Andreu-Vázquez, Cristina; Fernández, Rocío; Pastor-Tiburón, Natalia; Alvarado, Alberto; Carrero, Alicia; Fernández-Novo, Aitor; Esperón, Fernando; González, Fernando (Veterinary Sciences, 2023)
SIMPLE SUMMARY: Parasitism is one of the most common life strategies on Earth, where the host and the parasite establish a successful relationship and continually adapt to each other. Most of the studies on wild birds show that those with hemoparasites are usually asymptomatic due to this host–parasite coevolution, so blood parasites are often detected as incidental laboratory findings. Most of these studies have been performed mainly in passerines and migratory species, but nocturnal raptors seem to be more exposed to blood parasite vectors than other avian species due to their behavior and distribution. Blood samples were collected from 134 individuals during a four-year period to assess the occurrence of blood parasites and parasitemia in different species of nocturnal raptors and their effect on hematological parameters. Thirty-five percent (95% CI: 27.5–43.5%) of individuals included in the study tested positive for at least one hemoparasite genus, and 11.2% showed coinfection. Leucocytozoon was the genus most frequently detected (32.1%), followed by Haemoproteus (11.2%), Trypanosoma and Plasmodium (2.2% each). The Eurasian eagle-owl (Bubo bubo) was the species with the highest prevalence (94.7%). Moderate anemia and an increase in leukocyte counts were detected in the positive birds. Moreover, the positive animals showed a poor body condition score. ABSTRACT: Most hemoparasites hosted by wild birds appear to be harmless, but most of the blood parasite studies in avian wildlife are mainly focused on passerines or migratory species. This study aimed to assess the occurrence of blood parasites in nocturnal raptors (Strigiformes order) and their effect on hematological parameters. A total of 134 blood samples were collected during a four-year period for hematological analysis and hemoparasite detection and quantification by microscopical examination of the samples. Overall, the occurrence of hemoparasites was 35.1%, with Leucocytozoon being the most frequently detected (32.1%), followed by Haemoproteus ...